Optimasi Portofolio Saham Syariah dan Konvensional di Bursa Malaysia: Perbandingan Model Markowitz dan Algoritma Genetika - Deni Adelya Nurhayati; Dwi Eko Waluyo; Maria Safitri; Bara Zaretta (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study compares portfolio optimization performance between sharia-compliant stocks (FBM Hijrah Shariah Index) and conventional stocks (FTSE Bursa Malaysia KLCI) using the Markowitz Mean Variance Optimization (MVO) model and Genetic Algorithm (GA), evaluated through CV, Sharpe ratio, Sortino ratio, and Omega ratio over the period 2022–2025. Results show that the sharia portfolio consistently outperforms conventional across all metrics and both methods, with a Sharpe ratio of 0.1589 compared to 0.0709, demonstrating that sharia screening enhances rather than hinders portfolio efficiency. GA produces marginally higher Sharpe ratios than Markowitz, indicating both methods are complementary. These findings offer practical implications for investors, fund managers, and policymakers in developing competitive sharia investment instruments.